Epidemiology of extremity fractures in the Netherlands. Issue 7 (July 2017) - Beerekamp, M.S.H.; de Muinck Keizer, R.J.O.; Schep, N.W.L.; Ubbink, D.T.; Panneman, M.J.M.; Goslings, J.C.
Abstract: Introduction: Insight in epidemiologic data of extremity fractures is relevant to identify people at risk. By analyzing age- and gender specific fracture incidence and treatment patterns we may adjust future policy, take preventive measures and optimize health care management. Current epidemiologic data on extremity fractures and their treatment are scarce, outdated or aiming at a small spectrum of fractures. The aim of this study was to assess trends in incidence and treatment of extremity fractures between 2004 and 2012 in relation to gender and age. Methods: We used a combination of national registries of patients aged ≥ 16 years with extremity fractures. Fractures were coded by the International Classification of Diseases (ICD) 10, and allocated to an anatomic region. ICD-10 codes were used for combining the data of the registries. Absolute numbers, incidences, number of patients treated in university hospitals and surgically treated patients were reported. A binary logistic regression was used to calculate trends during the study period. Results: From 2004 to 2012 the Dutch population aged ≥16 years grew from 13, 047, 018 to 13, 639, 412 inhabitants, particularly in the higher age groups of 46 years and older. The absolute number of extremity fractures increased significantly from 129, 188 to 176, 129 (OR 1.308 [1.299–1.318]), except for forearm and lower leg fractures. Incidences increased significantly (3–4%) for wrist, hand/finger, hip/upper leg, ankle and foot/toe fractures. In contrast to the older age categories from 66 years and older, in younger age categories from 16 to 35 years, fractures of the extremities were more frequent in men than in women. Treatments gradually moved towards non-university hospitals for all except forearm fractures. Both relative and absolute numbers increased for surgical treatments of clavicle/shoulder, forearm, wrist and hand/finger fractures. Contrarily, lower extremity fractures showed an increase in non-surgical treatment, except for lower leg fractures. Conclusion: During the study period, we observed an increasing incidence of extremity fractures and a shift towards surgical treatment. Patient numbers in university hospitals declined. If these trends continue, policy makers would be well advised to consider the changing demands in extremity fracture treatment and pro-actively increase capacity and resources.